Impact of preterm premature rupture of membranes and oligohydramnios on in-hospital outcomes of very-low-birthweight infants. (31st December 2023) - Kim, Min Soo; Kim, Sol; Seo, Yumi; Oh, Moon-Yeon; Yum, Sook Kyung
Abstract: Objective: To analyze neonatal outcomes in very-low-birthweight (VLBW) infants depending on the presence of preterm premature rupture of membranes (PPROM), oligohydramnios, or both. Methods: The electronic medical records of VLBW infants admitted during the study period, January 2013 to September 2018, were reviewed. Neonatal outcomes (primary outcome: neonatal death; secondary outcome: neonatal morbidity) were compared depending on whether the infant was affected by PPROM or oligohydramnios. Logistic regression analysis was performed to assess the association of PPROM and oligohydramnios with neonatal outcomes. Results: Three hundred and nineteen VLBW infants were included: (1) 141 infants in the PPROM group vs. 178 infants in the non-PPROM group, and (2) 54 infants in the oligohydramnios group vs. 265 infants in the non-oligohydramnios group. The infants affected by PPROM were at significantly younger gestational ages at birth with lower 5-min Apgar scores than those not affected by PPROM. Histologic chorioamnionitis was significantly more frequent in the PPROM group than in the non-PPROM group. The proportions of small-for-gestational-age infants and infants affected by multiple births were significantly higher in the non-PPROM group. The median (interquartile range) PPROM latency and onset were 50.5 (9.0 − 103.0) h and 26.6 (24.1 − 28.5) weeks, respectively. Based on the logistic regression analysis assessing the association of PPROM and oligohydramnios with the significant neonatal outcome, oligohydramnios was significantly associated with neonatal death (odds ratio [OR] = 2.831, 95% confidence interval [CI] 1.447 − 5.539), air leak syndrome (OR = 2.692, 95% CI 1.224 − 5.921), and persistent pulmonary hypertension (PPH) (OR = 2.380, 95% CI 1.244 − 4.555). PPROM per se was not associated with any neonatal outcome. However, early onset PPROM and prolonged PPROM latency were associated with neonatal morbidity and mortality. When PPROM was accompanied by oligohydramnios, it was associated with increased odds for PPH (OR = 2.840, 95% CI 1.335 − 6.044), retinopathy of prematurity (OR = 3.308, 95% CI 1.325 − 8.259), and neonatal death (OR = 2.282, 95% CI 1.021 − 5.103). Conclusion: PPROM and oligohydramnios affect neonatal outcomes differently. Oligohydramnios, but not PPROM, is a significant risk factor for adverse neonatal outcomes, which is presumably related to pulmonary hypoplasia. Prenatal inflammation appears to complicate neonatal outcomes in infants affected by early PPROM and prolonged PPROM latency.